2019
DOI: 10.3390/foods8080323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Cooking Methods on Technological and Sensory Quality of Atlantic Salmon (Salmo salar)

Abstract: The aim of the study was to evaluate the effect of heat treatment salmon quality using the sous-vide method (57 °C, 20 min and 63 °C, 80 min) in comparison with traditional methods (steam cooking, roasting). The yield of process and sensory quality (sensory profile, consumer liking) and the color and texture of salmon was measured. Salmon processed with the sous-vide method was characterized by a statistically significantly (p ≤ 0.05) higher yield and water content than the samples prepared by steaming and roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 40 publications
0
25
1
1
Order By: Relevance
“…Previous studies [9,16,[20][21][22][23][24] discuss salmon prepared by sous-vide, but in a different context than our study. Our recent results [24] revealed that low parameter sous-vide processes resulted in products with similar characteristics to raw salmon, while higher parameters achieve a high intensity cooked fish odor and flavor without significant deterioration in texture.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Previous studies [9,16,[20][21][22][23][24] discuss salmon prepared by sous-vide, but in a different context than our study. Our recent results [24] revealed that low parameter sous-vide processes resulted in products with similar characteristics to raw salmon, while higher parameters achieve a high intensity cooked fish odor and flavor without significant deterioration in texture.…”
Section: Introductioncontrasting
confidence: 62%
“…Previous research has described the influence of these factors on the quality (including the nutritional value, and sensory and microbiological quality) of different fish species [17][18][19]. Previous studies [9,16,[20][21][22][23][24] discuss salmon prepared by sous-vide, but in a different context than our study. Our recent results [24] revealed that low parameter sous-vide processes resulted in products with similar characteristics to raw salmon, while higher parameters achieve a high intensity cooked fish odor and flavor without significant deterioration in texture.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Multi-layer, non-gas-permeable plastic packaging, which is also resistant to high temperature, minimizes the loss of nutrients and water and protects vitamins from degradation during exposure to high temperatures [ 42 ]. Moreover, it enables obtaining more juicy, tender and flavorful meat and fish products than high-temperature cooking methods [ 43 , 44 ]. In the current study, sous-vide cooking performed at a lower temperature (60 °C), but for a longer time (75 min), did not cause significant ( p < 0.05) folate losses compared with raw liver ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%